Titus Novus. Emperor Francis I's Iconography of Power and Its Reception in Croatia and Dalmatia - Špikić, Marko (Array, 2012)
The article deals with the perception of imperial persona of Francis I (II) of Austria in Croatia and Dalmatia around 1818 when Emperor visited the two regions of today’s Croatia. There are two principal sources of interpretation of the reign and importance of this ruler: the written and the visual. Until recently, Francis and his co-ruler count Metternich were in Croatian historiography generally considered in negative terms. This text offers a revision of these views. Following the already traditional Habsburg propaganda of the Imperial liberalitas, Francis was in 1818 received by his subjects in Croatia and Dalmatia as a long-awaited Emperor, with new epigraphic, commemorative monuments (triumphal arches, sculptures, pyramids) and, most frequently, with literary compositions in poetry, drama and prose. The examples of such gestures are taken from Zagreb, Zadar, Split and Dubrovnik. Although Francis’ Imperial epithets were various, the author focuses on the Italian variant, nuovo Tito, explaining the connections of the Imperial propaganda with its artistic response at the end of the 18th century.